San Marino : Financial Sector Assessment Program; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2010)
Stress tests indicate that the main vulnerabilities of the banking sector of San Marino relate to deposit outflows or to a deterioration of credit quality, and these risks are particularly high for the largest bank. There is no effective mechanism to provide liquidity to banks. The nonbank financial sector in San Marino consists of just over 50 small companies, but has growth potential. The governing body of the Central Bank of San Marino (CBSM) should be subject to clearer and stronger accountability, and be more independent from the government.